Tetragonia tetragonioides (Pall.) Kuntze protects estrogen-deficient rats against disturbances of energy and glucose metabolism and decreases proinflammatory cytokines - Ryuk, Jin Ah (Exp Biol Med (Maywood), 2016)
Tetragonia tetragonioides (Pall.) Kuntze (TTK) and JakYakGamCho-Tang (JGT) have been used for improving women’s health and treating inflammatory diseases. We determined that the long-term consumption of these herbal extracts alleviates the progression of postmenopausal symptoms in high-fat-diet fed ovariectomized (OVX) rats, and further explored the mechanisms involved. Five groups of OVX rats were fed high fat diets that were supplemented with either 2% dextrin (control), 2% TTK (70% ethanol extract), 2% JGT (water extract), 1% JGT + 1% TTK (JGTT), or 30 µg/kg body weight/day of 17β-estradiol (positive control). After eight weeks of dietary intervention, the herbal treatments did not change the serum concentrations of 17β-estradiol or uterine weight in control rats, but they were higher in the positive-control group. TTK rats exhibited higher daily energy expenditure, particularly fat oxidation, without modifying the energy intake than the controls. TTK lowered the fat mass but lean body mass of the abdomen and leg were increased. JGT decreased periuterine fat mass and lean body mass more than the control but the decrease was not as much as TTK. TTK resulted in substantially lower serum concentrations of the proinflammatory cytokines, tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1, than the control and JGT had lesser effect than TTK. Insulin resistance, determined by homeostasis model assessment estimate for assessing insulin resistance (HOMA-IR) and insulin tolerance test, was reduced in the decreasing order of control, JGT, JGTT, and TTK and the HOMA-IR of TTK was similar to the positive control. TTK, but not JGT, enhanced glucose tolerance compared with the control, although the serum insulin levels in TTK were lower compared to the control. Interestingly, the β-cell masses were much greater in the TTK and JGTT groups than in the control, and they were comparable to the positive control. The increases in β-cell masses in TTK and JGTT groups were associated with enhanced β-cell proliferation and suppressed apoptosis, which was related to the decreased TNF-α and interleukin-1β expressions. In conclusion, JGTT did not improve menopausal symptoms better than TTK itself. TTK itself prevented the OVX-induced impairments in energy, lipid, and glucose metabolism, similar to the positive control, without changing serum 17β-estradiol levels and potentiating insulin signaling and decreasing proinflammatory cytokines. TTK may be a useful intervention to alleviate some menopausal symptoms similar to selective estrogen receptor modulators and should be investigated with further human study. IMPACT STATEMENT: Menopause decreases the quality of life in middle-aged women and herbal remedies are sometimes used as alternatives for hormone replacement therapy, which may have detrimental side effects. Although several herbal extracts have been studied, no remedies improve all the menopausal symptoms. In this study, the 70% ethanol extract of Tetragonia tetragonioides (Pall.) Kuntze (TTK) reduced the symptoms of hot flushes and improved energy, glucose, and lipid metabolism in estrogen-deficient animals without increasing serum 17β-estradiol levels. This extract acts like a selective estrogen receptor modulator and it may be a useful intervention for alleviating menopausal symptoms. This is the first study to show that the 70% ethanol extract of TTK has the potential to treat menopause-associated symptoms and metabolic disturbances. It may be a useful intervention for alleviating the symptoms of menopause in women if its efficacy can be confirmed in human studies.